Availability, use, and consumption practices of ready-to-use therapeutic foods prescribed to children with uncomplicated severe acute malnutrition aged 6–59 months during outpatient treatment in Burkina Faso. (1st January 2022) - Nikièma, Victor; Fogny, Nadia F.; Kangas, Suvi T.; Lachat, Carl; Salpéteur, Cécile
Abstract: Ready-to-use-therapeutic-foods (RUTF) was designed for the nutritional management of children with uncomplicated severe acute malnutrition (SAM) treated as outpatients. However, to our knowledge, no study has evaluated the availability, use and consumption of RUTF within the beneficiary household in programs and in the context of a reduction in the dose of RUTF. This study, assessed the effect of a reduction in RUTF dose on the availability, use, consumption, and perceptions of caregivers on RUTF prescribed to 516 children treated for SAM, aged 6–59 months in Burkina Faso. Children received a weekly dose of RUTF according to their treatment arm until recovery. Data were collected by structured individual in-depth interviews, with caregivers one month and two months post-admission. Differences between children receiving reduced RUTF (intervention arm) and those receiving standard RUTF (control arm) were assessed by Poisson, logistic, and ordered logistic regression model. RUTF was available for the whole week in 95% in intervention arm compared to about 98% in control arm (p > 0.05). Starting from week 3 onwards, children in intervention arm consumed an average of 9 sachets of RUTF per week compared to 15 sachets in control arm (p < 0.001) and 5% of children in intervention arm reported leftover compared to 11% in control arm (p < 0.05). About 40% of children in intervention arm consumed RUTF at least 3-times per day compared to 82% in control arm (p < 0.001). The amount of RUTF prescribed was perceived as sufficient in 93% by caregivers in intervention arm against 97% in control arm (p > 0.05). In conclusion, reducing the dose of RUTF did not affect the availability of RUTF during treatment but did reduce leftover and the frequency of consumption of RUTF.